Dynamics of cilia length in left–right development - Pintado, P. (2017)
This work was supported by the Fundacao para a Ciencia e a Tecnologia (FCT-ANR/BEX-BID/0153/2012 research grant). T.D.M.-J. was supported by a Royal Commission for the Exhibition of 1851 Fellowship. S.S.L. was funded by FCT Investigator IF/00951/2012. B.T. was funded by FCT fellowship SFRH/BPD/77258/2011 and P.P. and P.S. were funded by the FCT-ANR/BEX-BID/0153/2012 research grant.